2021
DOI: 10.1016/j.ijcha.2021.100854
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance in recovering COVID-19 patients. Feature tracking and mapping analysis to detect persistent myocardial involvement

Abstract: Background Post-COVID-19 patients may incur myocardial involvement secondary to systemic inflammation. Our aim was to detect possible oedema/diffuse fibrosis using cardiac magnetic resonance imaging (CMR) mapping and to study myocardial deformation of the left ventricle (LV) using feature tracking (FT). Methods Prospective analysis of consecutively recruited post-COVID-19 patients undergoing CMR. T1 and T2 mapping sequences were acquired and FT analysis was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 40 publications
(56 reference statements)
3
34
0
Order By: Relevance
“…Four of the studies presented two cohorts [ 8 , 10 , 21 , 31 ]; therefore, we included a total of 33 independent cohorts. Among the 29 included studies, nine were from the USA [ 8 , 15 , 20 , 22 , 24 , 32 , 36 38 ], six were from China [ 10 , 11 , 16 , 18 , 21 , 30 ], three each from the UK [ 19 , 22 , 26 ] and Germany [ 7 , 23 , 28 , 35 ], two each from Italy [ 9 , 27 ] and Turkey [ 29 , 31 ], and one each from Poland [ 17 ], Norway [ 34 ], Hungary [ 33 ] and Spain [ 25 ]. The publication year was 2020 or 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies presented two cohorts [ 8 , 10 , 21 , 31 ]; therefore, we included a total of 33 independent cohorts. Among the 29 included studies, nine were from the USA [ 8 , 15 , 20 , 22 , 24 , 32 , 36 38 ], six were from China [ 10 , 11 , 16 , 18 , 21 , 30 ], three each from the UK [ 19 , 22 , 26 ] and Germany [ 7 , 23 , 28 , 35 ], two each from Italy [ 9 , 27 ] and Turkey [ 29 , 31 ], and one each from Poland [ 17 ], Norway [ 34 ], Hungary [ 33 ] and Spain [ 25 ]. The publication year was 2020 or 2021 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A CMR study by Urmeneta Ulloa et al [25] demonstrated higher T2 mapping values in patients recovering from COVID-19 infection compared to healthy controls, consisting of residual edema, while no differences were found in T1 mapping values or feature tracking. It must be noted that while myocardial involvement, defined by troponin level increases, in patients with COVID-19 can be relatively frequent and is associated with poor prognosis [26] , [27] , true myocarditis are relatively uncommon [16] , with 2.4 cases of definite or probable myocarditis per 1000 patients hospitalized with COVID-19 [21] .…”
Section: Myocarditismentioning
confidence: 98%
“… 50 Figure 3 illustrates an example of an approach to standardize the results for native T1 differences based on published studies that include T1 reference values from their own center. 22 , 48 - 50 , 75 , 76 , 78 , 80 , 83 - 85 , 87 , 93 - 95 This type of meta-analysis can identify factors, such as the time of recovery because time from infection onset is a source of disease-related variability of native myocardial T1 in COVID-19 survivors.…”
Section: Technical Considerations Regarding Heterogeneity In Lge and ...mentioning
confidence: 99%